Status Seeking and Work-Family Conflicts: How the Pursuit of Wealth and Success Threatens Family Peace in 26 Countries - Stephanie Hess; Christian Schneickert (Journal of Family and Economic Issues, 2024)
This paper takes a cross-national perspective and examines the association between the individual disposition to pursue wealth and success (status seeking) and work–family conflicts. We use data from the 2010 European Social Survey on more than 15,000 individuals from 26 countries who were of working age and living in families with children. The sample selection followed a stratified random sampling strategy and data were collected via computer-assisted personal interviews and pen and pencil interviews administered by trained interview personnel. Employing pooled and comparative single-country regression analyses as well as correlational analyses at the macro-level of countries, our results show that status seeking is related to higher levels of work–family conflict but that the strength of association is vastly different across countries. This individual-level effect is mainly driven by job characteristics and less so by socio-demographics in most of the countries studied. At the country level, better conditions for work and family reconciliation provided by welfare states dampen the effect of ambitiousness on work–family conflict, but only marginally. Interestingly, national wealth (GDP) strengthens the association, while differences in income inequality (Gini coefficient) among countries are not relevant in this regard. Our results highlight the need for a cross-national perspective when determining the antecedents of work–family conflicts.
Keywords: 300; Work-family conflict; Status seeking; National wealth; Income inequality; Family policies; Working conditions